2000
DOI: 10.1177/230949900000800203
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Pin Fixation in Clavicular Fractures: A Study Comparing the Use of Small and Large Pins

Abstract: The S-shaped clavicle poses a problem for intramedullary pin fixation. Stability of fracture fixation is closely related to the length of intramedullary pin engagement. This study was carried out to determine the engagement length of intramedullary pins into clavicular fractures using a small and a large pin. Seven pairs of fresh cadaveric clavicles were prepared and arranged into Group 1 and Group 2 for paired study. A mid-third clavicular fracture was created at the junction of the two curves of the clavicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Therefore, the favorable solutions for this might improve stability in IFs and reduce excessive movement in PFs especially in early-stage, postoperatively. In Harnroongroj’ and Lee’s studies, implant failure was attributed to the length of intramedullary pin engagement and small pin could provide better stability [ 17 , 39 ]. Authors suggested patients treated by PFs should gradually increase should motion range and keep within 90°during the first 3 weeks after surgery [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the favorable solutions for this might improve stability in IFs and reduce excessive movement in PFs especially in early-stage, postoperatively. In Harnroongroj’ and Lee’s studies, implant failure was attributed to the length of intramedullary pin engagement and small pin could provide better stability [ 17 , 39 ]. Authors suggested patients treated by PFs should gradually increase should motion range and keep within 90°during the first 3 weeks after surgery [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Although various techniques have been advocated for fracture fixation, including plating and intramedullary devices, only a few biomechanical studies provide the treating surgeon with information that may guide the selection of the most appropriate device for surgical repair. [12][13][14][15][16][17][18][19] Plating of middle third clavicular fractures has been supported in clinical studies as a successful and reproducible surgical option. 7,11,[20][21][22][23][24] Although debate has arisen over the ideal location for a plate, 12,19 biomechanical evidence has supported both superior and anterior plate locations depending on the fracture pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Both clinical and biomechanical studies support the use of intramedullary devices; however, the variability of implant designs has made the selection of the ideal implant difficult. [15][16][17][18] The purpose of this biomechanical study was to address the concept of ideal implant selection for the treatment of middle third clavicular fractures. Using a standardized testing protocol, four implants commonly used in modern orthopaedic practice were tested and compared in a simulated middle third clavicular fracture model.…”
Section: Introductionmentioning
confidence: 99%
“… 40 , 41 Therefore, to prevent this complication, the stability of IF needs to be improved, and excessive movement, especially in the early stages of recovery from PF surgery, should be minimized. 15 , 26 , 42 …”
Section: Discussionmentioning
confidence: 99%